EVALUATION OF MEDICAL ADHERENCE BASED ON THE HEALTH BELIEF MODEL THEORY AND GIVING PILL CARD TO HIV PATIENTS IN ONE OF THE COMMUNITY HEATH CENTER IN BANDUNG CITY - Quamila Akbarani, Shafa
Adherence to medication is very important for HIV patients. If patients are not adherent to treatment, the risk of disease and drug resistance will worsen. Pillcard administration will be used as a method to improve medication adherence in patients. The Health Belief Model theory is also used in assessing patient perceptions of medication adherence. This study aims to determine the effect of Pillcard administration on patient medication adherence and patient perceptions of medication adherence. The research method used was experimental research with a preexperimental design type one group pretest-posttest design. This study was conducted from February to April 2023 and involved 93 HIV patients at one of the public health centers in Bandung City. Data on medication adherence was obtained from the Medication Report Adherence Scale (MARS-5) questionnaire and Pillcount. Data on patient perceptions of medication adherence based on the Health Belief Model theory were assessed using a valid and reliable questionnaire. Statistical analysis related to the effect of Pillcard on adherence and patient perception will be obtained using the Wilcoxon signed-rank test method. Pillcard administration here was shown to significantly improve patient medication adherence both based on assessment using the MARS-5 questionnaire (p<0.000) and the pillcount method (p=0.001). HIV patients' perceptions of medication adherence based on the 6 dimensions of the health belief model theory after Pillcard administration also experienced significant changes. Namely in the perception of perceived vulnerability (p=0.000), perceived severity (p=0.000), perceived benefits (p=0.008), perceived barriers (p=0.000), perceived confidence (p=0.001), and cues to action (p=0.000) to treatment adherence behavior.